Development of a behavioural support intervention for e-bike use in Australia - Jenna McVicar; Rebecca Nourse; Michelle A. Keske; Ralph Maddison (BMC Public Health, 2022)
Abstract Background Insufficient physical activity (PA) is a risk factor for the development of many non-communicable diseases. Electric bicycles (e-bikes) offer considerable potential to support people to be physically active, however, no previous e-bike intervention studies have supported e-bike use with behavioural support. The aim of this study was to co-develop theory-based intervention components which can be used to increase physical activity through e-cycling among people who are overweight or obese and physically inactive. Methods We conducted a mixed-methods study using an online survey and virtual co-design workshops. We utilised the Behaviour Change Wheel (BCW) to inform the development of the behavioural support intervention to facilitate day-to-day e-cycling. Results One hundred participants completed an online survey and seven participated in the online co-design workshops. The development of the intervention identified five intervention functions (enablement, training, environmental restructuring, education, and persuasion) and 16 behaviour change techniques (BCTs) from 11 BCT groups (goals and planning, feedback and monitoring, social support, shaping knowledge, natural consequences, comparison of behaviour, associations, repetition and substitution, comparison of outcomes, antecedents, and self-belief). Conclusion To our knowledge, this is the first study to combine co-design and the BCW to develop a comprehensive behavioural support intervention for e-bike use. Theory based intervention options should be considered when providing e-bikes to individuals to help them increase their habitual PA levels.